12 Semi-Quantitative and Quantitative Analysis of Breast DCE-MRI (Breast MRI Interpretation, 2021)
Routine clinical interpretation of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) by radiologists is based on subjective assessment of signal enhancement and the change in signal intensity as a function of time after the injection of contrast media. This chapter reviews semi-quantitative and quantitative methods that can help Radiologists to more accurately diagnose cancers by providing standardized MRI parameters that are markers for malignancy. Semiquantitative analysis of DCE-MRI data provides parameters such as rate of signal enhancement and the decay of enhancement during contrast media washout. Semiquantitative approaches are relatively simple to implement in routine clinical practice, as these approaches do not require specialized acquisitions or complicated calculations. Quantitative methods have potential to standardize diagnosis by correcting for variations in Radiologists’ expertise, scanner performance, and the systemic physiology of the patient (e.g. cardiac output). In addition, quantitative methods attempt to relate MRI measurements directly to intrinsic properties of tissue, such as blood flow and capillary permeability. In this chapter we discuss a number of widely used semi-quantitative and quantitative methods for DCE-MRI including the “three time point method,” use of empirical mathematical models, use of compartmental models, impulse response analysis, reference tissue methods, and calibration methods required for quantitative measurements.
Keywords: dynamic contrast-enhanced MRI \; quantitative MRI; two compartment model; empirical mathematical model; Brix model; Patlak model; compressed sensing; impulse response analysis; reference tissue methods